KEPUASAN KERJA DAN MASA KERJA SEBAGAI PREDIKTOR KOMITMEN ORGANISASI PADA KARYAWAN PT ROYAL KORINDAH DI PURBALINGGA - Purida Kingkin; Haryanto Fadholan Rasyid; Ruseno Arjanggi (Faculty of Psychology Universitas Islam Sultan Agung Semarang, 2010)
This study aimed to verify empirically the relationship between job satisfaction and years of service with the commitment of the organization, know how big contribution of job satisfaction, organizational commitment and know how big contribution of years of service with the commitment of the organization. The population in this study as part of its permanent employees with monthly samples of 50 department employees and use of purposive sampling quota. This research data collection methods using scales. There are three hypotheses. Major hypothesis of this study is there a connection between job satisfaction and years of service with the organization's commitment to the employees of Royal Korindah in Purbalingga. Minor first hypothesis of this study is there a positive relationship between job satisfaction, organizational commitment to the employees of Royal Korindah in Purbalingga. Minor second hypothesis of this study is there a relationship between years of service with the organization's commitment to the employees of Royal Korindah in Purbalingga. Conclusion The results indicate that there is a significant relationship between job satisfaction and years of service with the organization's commitment to the employees of Royal Korindah in Purbalingga, there was a significant positive relationship between job satisfaction and organizational commitment and there wass a significant positive relationship between years of service with the commitment of the organization. Â Keywords: Organizational Commitment, Job Satisfaction and Work Period.